Prevalence of hydatid cyst in human and animals in Sulaimaniya city and Saedsadq distract - Mohamad, Mohamad O.; Al-taie, Lazem H.; Amin, Hersh A. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Hydatid disease is widespread and considered endemic in the Middle East and the Mediterranean, Iraq is one of the countries with a high endemicity of thisdisease.Objectives: The aim of this study is to diagnose hydatidosis and to identify the prevalence in human and animals in two different areas Sulaimaniya governoratewhich include Sulaimaniya city and Saedsadq district.,Methods: Seroepidemiological survey was conducted by using enzyme-linked immunosorbent assay (ELISA) and Indirect Haemagglutination IHA to detect antiEchinococcus granulosus antibody in random blood samples (536) of different sex, ages, and occupation out patients, in Sulaimaniya and Saedsadq. In the animal studyinspection and examination of the internal organs (liver, lungs, spleen and heart) Results: The Seropositivty in Saedsadq was higher( 3.7% )than in Sulaimaniya( 2.5%), and in female (2.8%, 6.4%) were higher than in male (1.6%, 1.2%)respectively both in Sulaimaniya and Saedsadq. In animal study results revealed that In Sulaimaniya infection rates were (1.5% of sheep, 0.5% of goats and 0.2% ofcattle), less than in Saedsadq (7.5%, 2.8% and 1.7%) respectively,Conclusion: The seropositive was higher in Saedsadq than Sulaimaniya , and higher among females than males in all age groups. The prevalence and fertility of hydatidcysts in sheep is higher than goat and cattle, sheep. Liver is the main involved organ.